Seroprevalence of past dengue virus infection among children and adolescents in Singapore. Issue 12 (25th June 2015) - Ang, Li Wei; Cutter, Jeffery; James, Lyn; Goh, Kee Tai
<x xml:space="preserve">Abstract</x> We conducted a pediatric seroprevalence study of dengue virus (DENV) infection in Singapore, a dengue endemic city‐state. Residual sera from 1, 200 Singapore residents aged 1–17 years seen in two hospitals between 2008 and 2010 were tested for anti‐DENV IgG antibodies. The overall seroprevalence was 10.4% (95%CI: 8.7–12.1%). There had been a marked decline in seroprevalence in the 15–19‐year age group over the last three decades, while the prevalence in the 1–5‐year olds (12.6%) was significantly higher than that of the 1996–1997 pediatric survey (0.8%). The overall dengue seroprevalence in children and adolescents remained low. J. Med. Virol. 87:2159–2162, 2015. © 2015 Wiley Periodicals, Inc.